2020
DOI: 10.1080/16549716.2020.1794107
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes among women born in Somalia and Sweden giving birth in the Stockholm area – a population-based study

Abstract: Background: Studies report that women born in some African countries, after migrating to the Nordic countries, have worse pregnancy outcomes than women born in the receiving countries. With the aim of identifying unmet needs among Somali-born women, we here study this subgroup. Objective: We compared pregnancy outcomes among women born in Somalia to women born in Sweden. Further, we investigated whether the proactive maternal observation of fetal movements has effects on birth outcomes among women born in Soma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…In line with previous studies, we reported an increased risk of Apgar score <7 at 5 minutes in specific immigrant groups 5,6,26 . Associations that have been suggested are prematurity, post‐term pregnancies, and suboptimal care during pregnancy and in labor 8 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with previous studies, we reported an increased risk of Apgar score <7 at 5 minutes in specific immigrant groups 5,6,26 . Associations that have been suggested are prematurity, post‐term pregnancies, and suboptimal care during pregnancy and in labor 8 .…”
Section: Discussionsupporting
confidence: 91%
“…In line with previous studies, we reported an increased risk of Apgar score <7 at 5 minutes in specific immigrant groups. 5,6,26 Associations that have been suggested are prematurity, post-term pregnancies, and suboptimal care during pregnancy and in labor. 8 Our material did not include premature births; but post-term pregnancies were more common among women born in low-income countries.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on migrant populations have shown that factors included are the process of migration, exposure to risks and access to the determinants of health in the country of origin (World Health Organization, 2018 ). Moreover, previous studies support that migration and adverse birth outcomes varies by migrant subgroup (Akselsson et al, 2020 ; Gagnon et al, 2011 ; Juarez et al, 2017 ; Urquia et al, 2010 ), with women from low-income countries being particularly vulnerable, having a 6.6 times higher maternal mortality rate compared to Swedish-born women (Esscher et al, 2013 ). Moreover, the destination country and the social circumstances that immigrants encounter in the new country affects immigrant’s health and adoption of unhealthy behaviours (Lindström & Sundquist, 2005; Lopez-Borbon, 2021 ).…”
Section: Introductionmentioning
confidence: 85%
“…For future research, to study the impact of major depression and antidepressant treatment, it would be of interest to study women born outside Sweden who later gave birth in Sweden since we know that migrant women have a higher risk for adverse maternal and neonatal outcomes (147,148).…”
Section: Future Perspectivesmentioning
confidence: 99%